2015
DOI: 10.1136/jech-2015-205848
|View full text |Cite
|
Sign up to set email alerts
|

Examining the link between women's exposure to stressful life events prior to conception and infant and toddler health: the role of birth weight

Abstract: Background The lifecourse perspective suggests a pathway may exist among maternal exposure to stressful life events prior to conception (PSLEs), infant birthweight, and subsequent offspring health, whereby PLSEs are part of a “chains-of-risk” that set children on a certain health pathway. No prior study has examined the link between PSLEs and offspring health in a nationally-representative sample of US mothers and their children. We used longitudinal, nationally-representative data to evaluate the relation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Results of the sensitivity analysis suggest that the study's findings are robust, and that maternal stress ranging from preconception throughout the gestational period is related to long-lasting effects on offspring development (e.g. [39][40][41][42][43][44][45]. The present results are consistent with the hypothesis that prenatal environmental stressors can affect reproductive systems through their effects on metabolism (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Results of the sensitivity analysis suggest that the study's findings are robust, and that maternal stress ranging from preconception throughout the gestational period is related to long-lasting effects on offspring development (e.g. [39][40][41][42][43][44][45]. The present results are consistent with the hypothesis that prenatal environmental stressors can affect reproductive systems through their effects on metabolism (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…This preconception group was included because maternal preconception stress, in the months and years before conception, has immediate and long-term postnatal effects on offspring development. [39][40][41][42][43][44][45] We assessed the degree of the women's objective exposure to the ice storm and their subjective distress. Their children have been evaluated on multiple developmental measures, including self-report data through questionnaires and face-to-face evaluations of their cognitive, behavioral, physical and motor development.…”
Section: Introductionmentioning
confidence: 99%
“…They found that gene involved in rhythmic process overpresented in irradiated male mice 24. Besides, transgenerational instability of the next generation was observed in Mughal et al’ study [ 22 ] because of a threshold dose of acute paternal irradiation. But the reasons why paternal exposure to radiation was associated with LBW still needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…24 ACEs also appear to have effects on the next generation, as preconception maternal early life adversity is associated with preterm birth and low birth weight, and maternal sexual abuse history independently predicts poorer birth outcomes. 5,6 Furthermore, maternal history of childhood abuse predicts hypothalamic–pituitary–adrenal (HPA) axis functioning in her offspring. 7 These findings are consistent with life course theory, which posits that health trajectories are influenced by recent events and reflect cumulative exposure, suggesting that consideration of both current stressors and experiences across a mother’s lifespan are needed to understand intergenerational health disparities.…”
mentioning
confidence: 99%